EDUKASI PEMANFAATAN TEKNOLOGI E-COMMERCE DALAM PEMASARAN PRODUK KELOMPOK SWADAYA MASYARAKAT DI KOTA PONTIANAK - Heniwati, Elok (Dharma: Jurnal Pengabdian Masyarakat, 2024)
Knowledge about marketing products and services by utilizing e-commerce technology is an obstacle faced by Kelompok Swadaya Masyarakat (KSM), encompassed in the Kotaku program, which Bappeda manages in the Pontianak City area, West Kalimantan Province. Thus, we conduct community service activities to give them an understanding of what and how e-commerce is helpful for marketing products or services. The PKM method used lectures and interactive discussions between the PKM team and participants. The results of the activity showed an increase in the understanding of participants regarding the role of e-commerce in supporting the marketing of their products or services. The next step is to provide assistance activities for KSM to create e-commerce for each existing KSM.